Association of Anaesthetists guidelines: cell salvage for peri‐operative blood conservation 2018. (10th July 2018) - Klein, A. A.; Bailey, C. R.; Charlton, A. J.; Evans, E.; Guckian‐Fisher, M.; McCrossan, R.; Nimmo, A. F.; Payne, S.; Shreeve, K.; Smith, J.; Torella, F.
Summary: The use of cell salvage is recommended when it can be expected to reduce the likelihood of allogeneic (donor) red cell transfusion and/or severe postoperative anaemia. We support and encourage a continued increase in the appropriate use of peri‐operative cell salvage and we recommend that it should be available for immediate use 24 h a day in any hospital undertaking surgery where blood loss is a recognised potential complication (other than minor/day case procedures).